The relation between neck strength and psychological distress: preliminary evidence from collegiate soccer athletes - Tara Porfido; Nicola L de Souza; Allison M Brown; Jennifer F Buckman; Brian D Fanning; James S Parrott; Carrie Esopenko (Concussion)
Aim: To examine whether neck strength and symmetry are associated with psychological function in athletes with exposure to repetitive head impacts. Methods: Collegiate soccer (n = 29) and limited/n...